Single amino acid change alters specificity of the multi-allelic wheat stem rust resistance locus SR9 - Zhang, Jianping; Nirmala, Jayaveeramuthu; Chen, Shisheng; Jost, Matthias; Steuernagel, Burkhard; Karafiatova, Mirka; Hewitt, Tim; Li, Hongna; Edae, Erena; Sharma, Keshav; Hoxha, Sami; Bhatt, Dhara; et al. (Nature communications, 2023)
Most rust resistance genes thus far isolated from wheat have a very limited number of functional alleles. Here, we report the isolation of most of the alleles at wheat stem rust resistance gene locus SR9. The seven previously reported resistance alleles (Sr9a, Sr9b, Sr9d, Sr9e, Sr9f, Sr9g, and Sr9h) are characterised using a synergistic strategy. Loss-of-function mutants and/or transgenic complementation are used to confirm Sr9b, two haplotypes of Sr9e (Sr9e_h1 and Sr9e_h2), Sr9g, and Sr9h. Each allele encodes a highly related nucleotide-binding site leucine-rich repeat (NB-LRR) type immune receptor, containing an unusual long LRR domain, that confers resistance to a unique spectrum of isolates of the wheat stem rust pathogen. The only SR9 protein effective against stem rust pathogen race TTKSK (Ug99), SR9H, differs from SR9B by a single amino acid. SR9B and SR9G resistance proteins are also distinguished by only a single amino acid. The SR9 allelic series found in the B subgenome are orthologs of wheat stem rust resistance gene Sr21 located in the A subgenome with around 85% identity in protein sequences. Together, our results show that functional diversification of allelic variants at the SR9 locus involves single and multiple amino acid changes that recognize isolates of wheat stem rust.
Keywords: alely; Amino Acid Sequence; mapování chromozomů; Haplotypes; haplotypy; Alleles; Chromosome Mapping; Basidiomycota; Disease Resistance; nemoci rostlin; odolnost vůči nemocem; sekvence aminokyselin; Plant Diseases